Workers rights are human rights : the case for linking trade and core labour standars = Los derechos laborales son derechos humanos : la razón para vincular el comercio y las normas fundamentales del trabajo - Philipson, Liz; Heyraud, Natalia (Brussels : Solidar, 1998)
Publicatie in twee delen én talen : Engels en Spaans
Engels
Spaans
Brochure
Keywords: mensenrechten